Review of Power-to-X Demonstration Projects in Europe - Wulf, Christina; Zapp, Petra; Schreiber, Andrea (Frontiers in Energy Research, 2020)
Core of most Power-to-X (PtX) concepts is the utilization of renewable electricity to produce hy-drogen via water electrolysis. This hydrogen can be used directly as final energy carrier or can be converted further into e.g. methane, synthesis gas, liquid fuels, electricity or chemicals. To inte-grate PtX into energy systems, technical demonstration and systems integration are of major im-portance. In total 220 PtX research and demonstration projects to analyze these issues have been realized, are already finished or in the planning in Europe by June 2020. Key issue of this review is the identification and assessment of relevant projects regarding year of commissioning, location, electricity and carbon dioxide sources, applied technologies for electrolysis, capacity, type of hy-drogen post-processing, as well as the aimed field of application. Latter changed over the years. At the beginning, it was fuel production, e.g. for hydrogen busses, and combined heat and power gen-eration, later injection into the natural gas grid. Today industrial applications and once again fuel production are important applications. Focus for the fuel production is synthetic gaseous fuels, while production of liquid fuels is severely under-represented. The SOEC (solid oxide electrolyzer cell) has a very small share in projects compared to PEM (polymer electrolyte membrane) and alka-line electrolyzers. This is also reflected by the different installed capacities. While alkaline electro-lyzers are installed with capacities between 50 and 5000 kW (2019/20) and PEM electrolyzers be-tween 100 and 6000 kW, SOEC have a size of 150 kW. France and Germany show the biggest ef-forts into the development of PtX technologies compared to other European countries. Overall, ac-tivities have progressed considerably faster than predicted just a couple of years ago.